2012
DOI: 10.5301/ejo.5000004
|View full text |Cite
|
Sign up to set email alerts
|

Topical Cyclosporine a Administration after Pterygium Surgery

Abstract: The results suggest that tCsA (Restasis, Allergan) can be used safely and effectively after pterygium surgery to obtain lower rates of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
1
8
1
5
Order By: Relevance
“…This is consistent to some extent with findings of a beneficial effect of topical cyclosporine in reducing recurrence [23].…”
Section: Medicationsupporting
confidence: 91%
“…This is consistent to some extent with findings of a beneficial effect of topical cyclosporine in reducing recurrence [23].…”
Section: Medicationsupporting
confidence: 91%
“…Tok et al , with almost twice as many patients, identified lower recurrence rates when ciclosporin was used: 12.9%. When ciclosporin is associated with conjunctival autograft it can decrease recurrence rates even more, as we can see in Aydin et al (3.4%) and Ozulkem56 (7.7%).…”
Section: Discussionmentioning
confidence: 68%
“…We observed [19]. Tok et al used cyclosporine following primary excision in primary pterygium cases, and observed the recurrence of 12.9% [13], Aydin et al who used topical cyclosporine with conjunctival limbal autograft observed a recurrence of 3.4% [20] and Ozulken K et al observed a recurrence of 7.7% with cyclosporine [21].…”
Section: Discussionmentioning
confidence: 69%